"Where's your bum brain?" Humor, social understanding, and sibling relationship quality in early childhood. Issue 2 (10th December 2020) - Paine, Amy L.; Karajian, Gassiaa; Hashmi, Salim; Persram, Ryan J.; Howe, Nina
Abstract: We investigated humor production in relation to social understanding and relationship quality in early childhood, by coding N  = 72 5‐year‐olds' ( M  = 5.78, SD  = .41) spontaneous humor production during play with an older ( n  = 34; M age = 7.84 years, SD  = .84) or younger sibling ( M age = 3.72 years, SD  = .54). Children who demonstrated better understanding of minds also produced more humor (preposterous statements and humorous anecdotes, and sound play). Types of humor were differentially associated with siblings' ratings of positive rapport; associations were moderated by sibling constellation factors. Our findings highlight children's humor production as an important marker of their understanding of minds and of their warm, positive relationships.